PEMENUHAN STANDAR NASIONAL PERPUSTAKAAN DI MADRASAH ALIYAH - Umul Hidayati (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
This research is conducted to identify the condition of libraries in Madrasah Aliyah (MA), whether they have fulfilled the national standard criteria of a library. This study uses the quantitative approach survey method and conducted in 9 provinces; West Java; Easst Java; Central Java; North Sumatera; NTB; South Kalimantan, West Kalimantan, NTT, and Maluku. This research indicates that the libraries in Madrasah Aliyah have not fulfilled the National standard criteria â€œStandar Nasional Perpustakaanâ€ (SNP) and the lack of fulfillment is calculated by the percentage of 49,6%. Among 7 variables of the research; the goal and use, the standard human resource, standard facility, standard collection, standard establishment and development of the library, 60,8% only belongs to the variable of standard establishment and development which is considered adequate for the SNP. On the other hand, the lowest variables in fulfilling the SNP are; the standard of facility, human resource, and goal and use of the library. One of the prominent factors of the SNPâ€™s lack fulfillment is the ineffective policy by the head of Madrasah in establishing libraries.